Estimación del indicador 15.3.1: Proporción de tierras degradadas en comparación con la superficie total de los municipios y territorios indígenas de Bolivia - Carlos Eduardo Quezada Lambertin; Marco Leandro Nina Vargas; Luz María Vigabriel Navarro (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2023)
– Monitoring land degradation processes is crucial for progressing towards the protection, restoration, and sustainable use of terrestrial ecosystems. In this study, the Sustainable Development Goal (SDG) Indicator 15.3.1, "proportion of degraded land over total land area," was estimated for 339 Municipalities and 197 Indigenous Territories in Bolivia. The findings reveal that between 2015 and 2021, land degradation in Bolivia encompassed 4.7% of the territory. However, there is significant variability at the municipal level, where 22 municipalities exhibited high degradation rates, exceeding 20%. These municipalities are primarily located in the Andean region, with degradation mainly due to land productivity loss. On the other hand, the largest area of degraded land is concentrated in the municipalities of the Santa Cruz department, mainly due to changes in land cover. In Indigenous Territories, the proportions of degraded land were considerably lower than in the municipalities, suggesting a higher effectiveness of these territories in controlling these processes. Lastly, it is recommended to conduct future studies with field validations to deepen the understanding of the causes promoting higher degradation, thereby designing strategies for the protection and restoration of terrestrial ecosystems according to the local conditions of each territory.
Keywords: Q01; Q2; Q24; 330; Indicator 15.3.1; Land Degradation; Sustainable Development Goals; Municipalities; Indigenous Territories